Influence Of Angularity Of Grains On Suffusion Process In Clayey Sand - Ari Sentani (International Conference on Coastal and Delta Areas, 2017)
About 46% from 136 dysfunctions of surveyed dams has related to internal erosion. Internal erosion is a phenomenon that is not fully understood, although it’s makes dysfunctions in dam’s structure. Two main phenomena responsible for erosion of particles in soil are backward erosion and suffusion. This report deals with suffusion process, which takes place inside the soil matrix. In suffusion, finer particles of a soil migrate within its own pore spaces be-tween the larger particles. These fine particles can be cohesionless particles or clay particles. With the objective to study the effect of angularity of coarse fraction grains on suffusion, a series of tests was performed on different clayey sand. Five sand types samples were tested which are different angularity of grains and same grain size distribution. Two experimental devices were used: one to characterize the grain shape and the second to quantify the influence of the grain shape on suffusion. Mechanical method was used to characterize the grain shape. By using a triaxial erodimeter, the suffusion sensitivity of five mixtures of kaolin-aggregates was determined. Results clearly demonstrate that suffusion process depends on the grain angularity of coarse fraction. With a constant flow, angularity of coarse fraction grains contributes to increase the suffusion resistance. Keywords: internal erosion, suffusion, triaxial erodimeter, angularity